EXPLORING THE RELATIONSHIP BETWEEN VOCABULARY MASTERY AND PLAGIARISM AMONG UNIVERSITY STUDENTS - Hartono, Dang Arif; Stefanus Angga Badara Prima; Jonathan Gultom; Wahyu Indriyo (English Education Study Program STKIP PGRI Pacitan, 2024)
This study investigates the relationship between vocabulary mastery and plagiarism among university students. Conducted at a private university in West Jakarta, Indonesia, it involved 71 students from various majors enrolled in a rhetoric and composition course. Using iThenticate to measure plagiarism and the Vocabulary Levels Test (VLT) to assess vocabulary proficiency, the research found a low average plagiarism rate of 11.56% in the students' essays. The study revealed no significant correlation between vocabulary mastery and the extent of plagiarism. Additionally, no substantial difference was observed in the amount of plagiarized content between students with lower and higher vocabulary proficiency. These findings suggest that vocabulary mastery alone may not be a significant factor in determining plagiarism behaviors, highlighting the multifaceted nature of plagiarism. The study underscores the need for further research into other potential contributors to plagiarism, such as psychological factors and cultural influences, and emphasizes the importance of teaching proper citation practices to combat academic dishonesty.